Construction of POMOFs with different degrees of interpenetration and the same topology. Issue 3 (25th November 2014) - Li, Liang; Sun, Jing-Wen; Sha, Jing-Quan; Li, Guang-Ming; Yan, Peng-Fei; Wang, Cheng
Abstract : Three POMOFs with different degrees of interpenetration are reported and the influence of the organic molecules on the degree of interpenetration of the compounds is discussed. Abstract : Three metal–organic networks with different degrees of interpenetration based on Keggin-type polyoxometalates have been hydrothermally synthesized by a simple change in the organic ligand and structurally characterized. By changing the length and the coordination mode of the ligand, we obtained compound1 which represents the first example of a three-fold interpenetrated POMOF architecture with pcu topology, and POMs occupy the vertex of the pcu lattice. Compound2 exhibits a POM-pillared metal–organic framework, which can be described overall as a two-fold interpenetrated pcu framework, and POMs occupy the arris of the pcu lattice. Different from1 and2, compound3 can be described as a single pcu network and POMs occupy the face of the pcu lattice. The influence of the organic ligand on the degree of interpenetration is also discussed. Furthermore, the results indicate that the three compounds present good photocatalytic activities.